Observing The Differences in Constitutional Court Decision About the Legal Age of Marriage - Mia Hadiati; Febriansyah Ramadhan (Jurnal Konstitusi, 2022)
In 2014–2017, there were two tests of the same norms in the Marriage Law, namely the Constitutional Court Decision Number 74 / PUU-XII / 2014 and 22 / PUU-XV / 2017. However, there is a difference in the verdict between one judgment and the next. In Constitutional Court Decision Number 22/PUU-XV/2017, the Constitutional Court changed the previous stance that stated that the age limit norm was constitutional, changing it to unconstitutional, which led to the follow-up of the lawmakers to revise the Marriage Law. This study will compare judges' considerations in the decisions of Constitutional Court Number 74 / PUU-XII / 2014 and Number 22 / PUU-XV / 2017. It will be sought against the Constitutional Court's background changing its stance from one ruling to the next. This research uses normative research methods with a conceptual and philosophical approach to legislation. The results showed that the difference underlying the two rulings was in the excavation of legal sources by judges in their legal considerations.